A Leader with the Vision of the Shared Future of Humanity - Glišin, Vanja (Napredak, 2024)
A shared future of humanity is the guiding idea of Chinese President Xi Jinping, as proved by numerous examples from his political practice, from his taking over the presidential function to date. A comprehensive and visionary approach of the Chinese president deserves attention, and that is why it is necessary to speak and write about it, particularly having in mind the idea of global peaceful progress and an open invitation to the countries worldwide to join common development and progress. Chinese President is aware that without developed China there is no developed world and vice versa, and that is why he puts huge efforts in the trade, economic, social, technological and political development of China and in the ideas of openness and cooperativeness with other countries in the world. Relying on traditional Chinese values and remembering the past, President Jinping committedly acts in the present with a vision of the prosperous future.